1985
DOI: 10.1017/s0022029900023852
|View full text |Cite
|
Sign up to set email alerts
|

Yield and composition of milk from Friesian cows grazing either perennial ryegrass or white clover in early lactation

Abstract: SUMMARYThe yield and composition of milk from Friesian cows grazing either perennial ryegrass (Lolium perenne) (G, ten cows) or white clover (Trifolium repens) (C, nine cows) were evaluated between d 21 and 129 post partum. The two forages, of similar digestible energy content, were the sole source of nutrients and were offeredad lib. (exp. 1). Digestion and flow at the duodenum were measured on 13 occasions in early lactation with comparable cows fitted with rumen and duodenal cannulae and grazing similar for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
2
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 22 publications
5
37
2
2
Order By: Relevance
“…Accessions growing in different climatic conditions could show different morphological and physiological characters. Similar to these genotypes in this study showed different genotypic variance inferring that the bigger genotypic variance the better breeding success (Açıkgöz 2001;Baker and Willıams 1987;Taylor 1985;Thomson 1985;Brock 1983;Brougham 1960). Minimum, maximums and mean values of plant characters are given in Table 1.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Accessions growing in different climatic conditions could show different morphological and physiological characters. Similar to these genotypes in this study showed different genotypic variance inferring that the bigger genotypic variance the better breeding success (Açıkgöz 2001;Baker and Willıams 1987;Taylor 1985;Thomson 1985;Brock 1983;Brougham 1960). Minimum, maximums and mean values of plant characters are given in Table 1.…”
Section: Resultssupporting
confidence: 62%
“…The erect genotypes are suitable to hay yield, but the other group prostrate genotypes are appropriate to be grazed (Açıkgöz 2001) Maintained that erect genotypes give more hay yield than prostrate ones. Prostrate genotypes are more resistant to for animal grazing and they could safely place in establishment meadow (Açıkgöz 2001;Baker and Willıams 1987;Taylor 1985;Thomson 1985;Brock 1983;Brougham 1960).…”
Section: Flowermentioning
confidence: 99%
“…However, this trend was not observed in plants grown in 2000, where the WSC content was more typical of that observed in field grown white clover. Thomson et al (1985) reported a mean WSC content of 102 g/kg DM in field-grown white clover over a 14-week period. The low herbage WSC contents, and the relationship with nitrate application level, suggest that the rate of carbon fixation was limiting at the time of harvest in experiment 1.…”
Section: Discussionmentioning
confidence: 99%
“…Thomson et al (1985) reported a mean N content of 44 g/kg DM in white clover over a growing season. In contrast to temperate grasses, it is difficult to manipulate the N content of legumes such as white clover, as N 2 fixation makes it difficult to restrict N supply.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, in these two trials, the type of flora (ryegrass or cooksfoot) that can have an effect on milk yield and composition (Demarquilly, 1963;Thompson et (Rowland, 1938), urea, phosphorus and calcium concentrations.…”
mentioning
confidence: 99%